Emotional climate among university students during the pandemic - Fernández, Anna María (Revista de Sociología, 2021)
The purpose of this study was to explore the emotions and feelings generated by the pandemic and isolation at home. A survey and a series of interviews were conducted online with a sample of students from a university in Mexico City. Results showed that the declaration of a health emergency caused fear, and that isolation at home provoked sadness. More generally, the pandemic had considerable psychological impact expressed through a wide range of emotions—sometimes apparently contradictory—according to individual experience. Such emotions typically arise in times of uncertainty and disruption to people’s lives as they attempt to adapt. However, if these emotions intensify or become chronic, they can lead to dysfunctionality and poor health.